Taksonomiczna miara rozwoju jako alternatywa względem miar ryzyka - Byrka-Kita, Katarzyna (Taxonomic Development Measure as an Alternative to Common Risk Measures, 2006)
As a result of the fact that ß coefficient cannot be considered as an adequate risk measure, alternative risk measures are developed and tested. The method which is multivariate comparative analysis is applied. The research included 1095 firms. Taxonomic methods allowed to rank various secretors of Polish economy according to the degree of risk.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1109, s. 103-115